2015
DOI: 10.1259/bjr.20140480
|View full text |Cite
|
Sign up to set email alerts
|

The superior aspect of the perirenal space: could it be depicted by dual-source CTin vivoin adults

Abstract: This study was conducted in vivo in adults by high-resolution DSCT, and more samples could be provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
(2 reference statements)
1
7
0
Order By: Relevance
“…1,5214,16-18, 21 Meyers et al 9 reported that the anterior renal fascia (retromesenteric plane) and the posterior renal fasciae (retrorenal plane) fused with each other on the lateral side; they were firmly fixed to each other above the adrenal gland and were connected to the diaphragmatic fascia. However, some investigators 15,21 reported that the renal fascia (retromesenteric plane) fuses with the parietal peritoneum at the level of attachment of the transverse mesocolon.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,5214,16-18, 21 Meyers et al 9 reported that the anterior renal fascia (retromesenteric plane) and the posterior renal fasciae (retrorenal plane) fused with each other on the lateral side; they were firmly fixed to each other above the adrenal gland and were connected to the diaphragmatic fascia. However, some investigators 15,21 reported that the renal fascia (retromesenteric plane) fuses with the parietal peritoneum at the level of attachment of the transverse mesocolon.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 140 patients suspected of having acute pancreatitis on MDCT, 134 were diagnosed as such based on diagnostic criteria. 24 Of these 134 patients, those with ascites surrounding the right retromesenteric plane (n 5 6), renal cell carcinoma (n 5 1), retroperitoneal neoplasms (n 5 2), hypoalbuminaemia (serum albumin level ,3.0 g dl 21 ; n 5 6) and a history of abdominal surgery (n 5 7) were excluded. The number of patients with acute pancreatitis in the final study group was 112 (73 males and 39 females; mean age, 61 years; age range, 21-89 years).…”
Section: Patient Selectionmentioning
confidence: 99%
See 3 more Smart Citations